Morgan Construction Company : managing five generations of family ownership - Kasouf, Chickery; Hoy, Frank; Pu, Hansong (London : SAGE Publications: SAGE Business Cases Originals, 2018)
In 2007, Philip (Flip) Morgan and his brother Dan were considering whether to accept an offer to sell the company and relinquish nearly 120 years and five generations of family ownership of the company that they led. Morgan was a leader in the development, building, and sale of rolling mills: metal forming capital equipment. When they entered the business early in their careers, both brothers expected to retain family ownership in the business. They oversaw significant global growth, and led an executive and engineering team that included relatively few family members. They were able to lead the firm through significant strategic shifts that required a long-term perspective while ownership was dispersed among more than 100 descendants of the founder. The central issue in the case is the Morgan brothers' decision about retaining ownership, but it is also a vehicle for discussing succession, intergenerational dynamics, and managing possible conflicts in ownership as the founder's family grows.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Morgan, Philip, -- active 2018.; Morgan, Dan, -- active 2018.; Morgan Construction Company; Family-owned business enterprises